Latin American perceptions of fear and exaggeration transmitted by the media with regard to COVID-19: frequency and association with severe mental pathologies - Mejia, Christian R.; Aveiro-Róbalo, Telmo Raul; Garlisi Torales, Luciana Daniela; Castro Hidalgo, Verónica Alejandra Alejandra; Valeriano, Jhino; Ibarra-Montenegro, David Alfonso; Conde-Escobar, Aram; Sánchez-Soto, Fernanda; Canaviri-Murillo, Yuliana; Oliva-Ponce, María; Serna-Alarcón, Victor; Vilela-Estrada, Martín A.; et al. (Frontiers in Psychology, 2023)
Introduction: This COVID-19 pandemic brought much misinformation by the media, which caused fear and concern. Objective: To determine the association between pathologies of the mental sphere and the perception of fear and exaggeration transmitted by the media with respect to COVID-19 in Latin America. Methodology: This is an analytic cross-sectional study, based on a validated survey to measure fear and exaggeration transmitted by the media and other sources (Cronbach’s Alpha: 0.90). We surveyed more than six thousand people, originally from twelve Latin American countries, associating this perceived exaggeration with stress, depression and anxiety (measured through DASS-21, Cronbach’s Alpha: 0.96). Results: Social networks (40%) or television (34%) were perceived as those who exaggerate the magnitude of the events; also, television (35%) and social networks (28%) are those who generate much fear. In contrast, physicians and health personnel are those who exaggerated less (10%) or provoked less fear (14%). Through multivariate model, we found a higher level of global perception which was associated according to whether being older (p=0,002), having severe or more serious anxiety (p=0,033), or stress (p=0,037). On the other hand, in comparison with Peru (the most affected country), there was a lower level of perception in Chile (p<0,001), Paraguay (p=0,001), Mexico (p<0,001), Ecuador (p=0,001), and Costa Rica (p=0,042). All of them were adjusted for gender, and having severe or major depression. Conclusion: There exist an association between some mental pathologies and the perception that the media does not provide moderate information.